Effectiveness and safety of edoxaban versus warfarin in patients with nonvalvular atrial fibrillation: a systematic review and meta-analysis of observational studies - Alsultan, Mohammed M.; Alahmari, Abdullah K.; Mahmoud, Mansour A.; Almalki, Ziyad S.; Alzlaiq, Wafa; Alqarni, Faisal; Alsultan, Fahad; Ahmed, Nehad Jaser; Alenazi, Ahmed O.; Scharf, Lucas; Guo, Jeff Jianfei (Frontiers in Pharmacology, 2023)
Background: Atrial fibrillation (AF) is the most prevalent cardiac arrhythmia type. Patients with AF are often administered anticoagulants to reduce the risk of ischemic stroke due to an irregular heartbeat. We evaluated the efficacy and safety of edoxaban versus warfarin in patients with nonvalvular AF by conducting an updated meta-analysis of real-world studies. Methods: In this comprehensive meta-analysis, we searched two databases, PubMed and EMBASE, and included retrospective cohort observational studies that compared edoxaban with warfarin in patients with nonvalvular AF from 1 January 2009, to 30 September 2023. The effectiveness and safety outcomes were ischemic stroke and major bleeding, respectively. In the final analysis, six retrospective observational studies involving 87,236 patients treated with warfarin and 40,933 patients treated with edoxaban were included. To analyze the data, we used a random-effects model to calculate the hazard ratio (HR). Results: Patients treated with edoxaban had a significantly lower risk of ischemic stroke [hazard ratio (HR) = 0.66; 95% confidence interval (CI) = 0.61–0.70; p < 0.0001] and major bleeding (HR = 0.58; 95% CI = 0.49–0.69; p < 0.0001) than those treated with warfarin. The sensitivity analysis results for ischemic stroke and major bleeding were as follows: HR = 0.66; 95% CI = 0.61–0.70; p < 0.0001 and HR = 0.58; 95% CI = 0.49–0.69; p < 0.0001, respectively. Conclusion: Our findings revealed that edoxaban performed better than warfarin against major bleeding and ischemic stroke.